Structural and Electrical Properties of "Cadmium Sulfide- Cobalt" Compound and Using it as a Gas Sensor (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2023)
Background: Both the cubic (zinc blend) and hexagonal (wurtzite) phases of cadmium sulphide are semiconductors due to the presence of a row of four equally spaced Cd atoms surrounded by one S atom. Both the cubic and hexagonal crystal forms of Cd-S have very similar nearest neighbor bond lengths. Material and Methods: The cadmium sulfide compound was prepared at a concentration of 1 M by dissolving the percentage by weight of each of cadmium(13.326g) and sulfur (3.806g) in 100 ml of distilled water. Cobalt was prepared at a concentration of 0.5M by dissolving a percentage by weight of Cobalt acetate (14.55g) in 100 ml of distilled water. Films CdS and CdS:Co were prepared using the chemical method, which is the thermal chemical spraying technique, which deposited a solution of cadmium sulfide mixture of cobalt solution with cadmium sulfide on a glass floor.Results: The thickness of the prepared films was 100 mm. The surfaces of the prepared films were studied by measuring transmission electron microscopy. The results showed that the prepared films are homogeneous and have crystalline granules of spherical shape, and the addition of cobalt to the cadmium sulfide compound led to an increase in the particle size values. The electrical properties represented by measuring the voltaic- current were studied, and the results showed that the relationship between the voltaic- current is linear, and this indicates that the prepared films behave as ohmic.Conclusion: The continuous electrical conductivity was also calculated, and the results showed that the addition of cobalt acetate to the cadmium sulfide compound led to an increase in the electrical conductivity values. The gas sensitivity of the prepared films towards hydrogen sulfide gas was studied, and the results showed that the prepared films had good sensitivity, and adding cobalt acetate to the cadmium sulfide compound led to a decrease in the sensitivity values.